2012
DOI: 10.1016/j.tine.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between approximate number system acuity and early symbolic number abilities

Abstract: a b s t r a c tThe present study assessed the relationships between approximate and exact number abilities in children with little formal instruction to ask (1) whether individual differences in acuity of the approximate system are related to basic abilities with symbolic numbers; and (2) whether the link between non-symbolic and symbolic number performance changes over the development. To address these questions, four different age groups of 3-to 6-year-old children were asked to compare pairs of train wagons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
84
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 48 publications
21
84
4
Order By: Relevance
“…Although inconsistent with some previous findings where ANS accuracy predicted mathematics attainment (Bonny & Lourenco, 2013;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2013Mussolin et al, 2012), the present results are consistent with a number of findings that have not found significant relations between tasks indexing the ANS and mathematics attainment (Göbel et al, 2014;Holloway & Ansari, 2009;Sasanguie, De Smedt et al, 2012;Sasanguie, van den Bussche et al, 2012). The pattern of our results (with the ANS supporting early calculation but not counting skills) suggests that the ANS has a differential influence on different number skills.…”
Section: Approximate Discriminationcontrasting
confidence: 92%
See 2 more Smart Citations
“…Although inconsistent with some previous findings where ANS accuracy predicted mathematics attainment (Bonny & Lourenco, 2013;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2013Mussolin et al, 2012), the present results are consistent with a number of findings that have not found significant relations between tasks indexing the ANS and mathematics attainment (Göbel et al, 2014;Holloway & Ansari, 2009;Sasanguie, De Smedt et al, 2012;Sasanguie, van den Bussche et al, 2012). The pattern of our results (with the ANS supporting early calculation but not counting skills) suggests that the ANS has a differential influence on different number skills.…”
Section: Approximate Discriminationcontrasting
confidence: 92%
“…Individual differences in approximate quantity discrimination tasks have been found to relate concurrently, retrospectively and longitudinally to mathematical attainment (e.g. Bonny & Lourenco, 2013;Halberda, Mazzocco, & Feigenson, 2008;Inglis et al, 2011;Libertus et al, 2011Libertus et al, , 2013Mussolin, Nys, Leybaert, & Content, 2012). However, other studies have failed to identify this relationship (Göbel, Watson, Lervåg, & Hulme, 2014;Holloway & Ansari, 2009;Kolkman, Kroesbergen, & Leseman, 2013;Lonnemann, Linkersdorfer, Hasselhorn, & Lindberg, 2011;Sasanguie, De Smedt, Defever, & Reynvoet, 2012;Sasanguie, van den Bussche, & Reynvoet, 2012;Soltész, Szucs, & Szucs, 2010) or suggested that this relationship is inconsistent over development (Bonny & Lourenco, 2013).…”
Section: The Approximate Number System (Ans)mentioning
confidence: 99%
See 1 more Smart Citation
“…Children who understood the exact meaning of the number words "one" to "six" at 3.5 years of age had significantly higher numerical preference scores in infancy than children who only understood a subset of those count words [t (38) = −2.70, P = 0.01], even though the groups did not differ in general intelligence (P > 0.2).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, infants as young as 48 h are able to differentiate ratios of 3:1 but not 2:1 (20), and, as they age, children show increasingly precise abilities: at 6 mo, they can distinguish ratios of 2:1, and by 9 mo, ratios of 3:2 (21,22). They eventually reach competencies for ratios 4:3 by 3 y, 6:5 by 6 y, and 8:7 and more difficult ratios by adulthood (23)(24)(25)(26). Furthermore, the ability to discriminate nonsymbolic number in childhood is predictive of later numerical discrimination abilities (27,28).…”
mentioning
confidence: 99%